Efeito do tratamento magnético da água nas diversas fases de Cultivo do camarão marinho Penaeus vannamei - Sousa, Rommel Rocha de (2019)
Compared to other countries, Brazilian shrimp farming has had a moderate development, occupying an area of less than 25,000 hectares. However, in recent years, shrimp production has accelerated in the Northeast due to increased domestic demand and improved technological processes. Magnetic water treatment is a simple feature in which water passes through a magnetic field and changes some of its physical-chemical properties. Recently, magnetism technology has been gradually applied in aquaculture to increase growth, breeding speed, reduction of mortality in ecdysis processes, enhancing immunity and larval production. The present project aims to research and evaluate the use of magnetically treated water in the larvae of Penaeus vannamei, at commercial level. The present study was developed at the companies CELM Ltda, located in Aracati-CE, Santorini Aquicultura Ltda., Located in Fortin-CE and Monólitos Aquicultura Ltda. For experiment 1, nauplii were used to perform larviculture from the subplot nauplii 4 (N4) to PL11, for a minimum period of 21 days, at CELM Ltda., With 2 treatments and 4 replications each, one treatment and a treatment with tanks counting magnetized water. For experiment 2, post-larvae were used for the cultivation during the secondary nursery phase from PL11 to animals of 0.6 g, for a minimum period of 30 days, at the company Santorini Aquicultura Ltda. Post-larvae (PL21) from experiment 3 were used, generating a total of 2 treatments with 2 replicates each, for commercial cultivation, being a control treatment and another treatment with larvae that passed through the nursery phase in magnetized water. In the maturation sector the magnetization technology was able to improve the reproductive parameters of the animals. In the larviculture the survival, the average weight and the productivity of the tanks were improved. There were no significant differences in the experiments of secondary nursery and commercial cultivation.